The First Assessment of Reading, 1970-71 Assessment. Released Exercise Set. No. 02-R-25 - Education Commission of the States, Denver, CO. National Assessment of Educational Progress; Education Commission of the States, Denver, CO. National Assessment of Educational Progress ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
This exercise set provides access to the 134 items released from the first National Assessment of Educational Progress (NAEP) reading assessment conducted in 1970-71 with students aged 9, 13, and 17. The exercises are intended for use by state and local education agencies who may want to build their own assessment instruments. An overview of the NAEP testing program and an explanation of the documentation provided for the test items is given. Each of the 134 items is displayed on a single page, and an accompanying page provides the following information: the theme of the exercise, the NAEP number, the objective, the administration mode, the age group and amount of time required to complete the exercise, and a breakdown by age, sex, and region of the students answering the item correctly. The test items are criterion-referenced and are based on the following eight themes or skills (1) understanding words and word relationships, (2) interpreting graphic materials, (3) understanding written directions, (4) using reference materials, (5) gleaning significant facts from passages, (6) finding main ideas, (7) drawing inferences, and (8) reading critically. (MKM) Primary type of information provided by report: Assessment Instrument (Released Exercises); Results (Exercise Level).
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Contract Number: OEC-0-74-0506.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Criterion Referenced Tests; Elementary Secondary Education; Minimum Competency Testing; National Competency Tests; Reading Achievement; Reading Skills; Reading Tests; Test Items; National Assessment of Educational Progress; Tests/Questionnaires.